Punk rock, so what? : the cultural legacy of punk - Sabin, Roger, 1961- (Routledge, 1999)
Punk Rock: So What? brings together a new generation of writers, journalists and scholars to provide the first comprehensive assessment of punk and its place in popular music history, culture and myth.